Pemberdayaan Masyarakat Melalui Pembudidayaan Stroberi di Desa Dalisodo - Devi Merina Tuz Sa’diyah (Pusat Riset dan Inovasi Nasional, 2024)
The focus of this study is to describe the empowerment of rural communities, especially residents learning the equality program at PKBM Mentari, through strawberry cultivation. The method used is a qualitative research method with the type of case study conducted in Kalisodo Village, Wagir. The main data sources used in compiling this article were obtained from interviews with two sources, namely